Effects of Climate Change on Dairy Cattle Production - Collier, Robert J; Bilby, Todd R; Rhoads, Michele E; Baumgard, h; Rhoads, Robert P (Annals of Arid Zone, 2016)
There are three dominant gene groups in the dairy cattle population [Bas taurus, Bas indicus and Sanga (hybrid of first two)] with varying levels of resistance to thermal stress. Bas taurus cattle have a greater sensitivity to elevated environmental conditions and superior resistance to cold stress than either Bas indiclls or Sanga, due to increased levels of endogenous heat production associated with increased milk production and feed intake. However, there are also molecular and phenotypic differences in hair coat characteristics and cellular responses to thermal stress as well. Climate change associated with greenhouse warming will have the greatest impact on Bas indiclls cattle populations, but will also adversely affect all breeds to some degree. New data suggests that the upper Temperature Humidity Index (THI) threshold for high-producing (>35 kg dÂ·l ) Bas taurus cattle should be a THI daily minimum of 65 and average THI of 68. There is also strong evidence that the upper threshold THI for reproduction is lower than that for lactation. However, several new management technologies are now available to help reduce the negative impact of thermal stress on cattle reproduction. Additionally, only half of the loss in milk yield to thermal stress can be accounted for by a decrease in feed intake with the remainder likely associated with altered carbohydrate and fat metabolism and/or direct effects on milk synthesis and secretion. This suggests that nutritional management strategies may provide opportunities to improve lactation performance of dairy cattle during periods of thermal stress. Key words: Climate, cattle, growth, lactation, reproduction, breed effects.